Lineage analysis of the late otocyst stage mouse inner ear by transuterine microinjection of a retroviral vector encoding alkaline phosphatase and an oligonucleotide library. - Han Jiang; Lingyan Wang; Kevin T Beier; Constance L Cepko; Donna M Fekete; John V Brigande (PLoS ONE)
The mammalian inner ear subserves the special senses of hearing and balance. The auditory and vestibular sensory epithelia consist of mechanically sensitive hair cells and associated supporting cells. Hearing loss and balance dysfunction are most frequently caused by compromise of hair cells and/or their innervating neurons. The development of gene- and cell-based therapeutics will benefit from a thorough understanding of the molecular basis of patterning and cell fate specification in the mammalian inner ear. This includes analyses of cell lineages and cell dispersals across anatomical boundaries (such as sensory versus nonsensory territories). The goal of this study was to conduct retroviral lineage analysis of the embryonic day 11.5(E11.5) mouse otic vesicle. A replication-defective retrovirus encoding human placental alkaline phosphatase (PLAP) and a variable 24-bp oligonucleotide tag was microinjected into the E11.5 mouse otocyst. PLAP-positive cells were microdissected from cryostat sections of the postnatal inner ear and subjected to nested PCR. PLAP-positive cells sharing the same sequence tag were assumed to have arisen from a common progenitor and are clonally related. Thirty five multicellular clones consisting of an average of 3.4 cells per clone were identified in the auditory and vestibular sensory epithelia, ganglia, spiral limbus, and stria vascularis. Vestibular hair cells in the posterior crista were related to one another, their supporting cells, and nonsensory epithelial cells lining the ampulla. In the organ of Corti, outer hair cells were related to a supporting cell type and were tightly clustered. By contrast, spiral ganglion neurons, interdental cells, and Claudius' cells were related to cells of the same type and could be dispersed over hundreds of microns. These data contribute new information about the developmental potential of mammalian otic precursors in vivo.